(untitled) (Perner’s Contacts, 2015)
This article is about transport of refrigerated or frozen cargo by refrigerated and freezer containers. There are also mentioned the reasons why this mode of transport was developed. We can find the information about the temperatures in which perishable cargo is transported. In the article there is also the description of the containers that are used by MAERSK company.